STAT: schema therapy for addiction treatment, a proposal for the integrative treatment of addictive disorders - Lacy, Elizabeth (Frontiers in Psychology, 2024)
The nature and origins of addictions and of their adjunctive behaviors, as well as their chronicity, call for treatments that conceptualize and treat them as the long-term and complex processes that they are. Addictions are often comorbid with personality problems and with trauma histories. Patients suffering from these disorders often show poor engagement with treatment and high rates of relapse, possibly because available treatments have yet to address the patient suffering from addiction in a more integrated or holistic manner. In particular, comprehensive treatment models for addictive disorders – like treatments for personality disorders or trauma – are likely to require the integration of behavioral, cognitive, and emotion-focused interventions within a facilitative therapeutic relationship. However, most current treatment models, including ones which are highly effective in stabilization or behavioral change, lack one or more components of treatment that could sustain longer term recovery, wellness, and health for a higher percentage of patients. In this article, I propose approaching addictions and their treatment from the perspective of schema therapy, an integrative, developmental model with a strong track record of positive outcomes in addressing personality disorder symptoms and long-standing trauma histories, commonly comorbid with addictive disorders. In advancing this proposal, I begin by providing some background tying together addictions, attachment, and personality, suggesting they be treated simultaneously to achieve improved outcomes. Then, after briefly reviewing the leading approaches to the treatment of addictions, I introduce the idea that schema therapy is well-situated – both theoretically and practically – to address many of the shortcomings of existing treatment options. In particular, I note how addictive and co-occurring colluding behaviors are deeply intertwined with both early and continued frustration of core developmental needs. I illustrate how the addictive cycle is perpetuated through the process of schema reinforcement and through the operation of schema modes. I then demonstrate how these key terms (i.e., needs, schemas, and modes) inform the patient’s assessment and case formulation, guiding treatment interventions from a strong therapeutic relationship that focuses on integrating recovery behavior change, healing dysfunctional schemas and modes, and preventing relapse.